PROBLEMS OF STUDENTS’ COMMUNICATION ABILITY BROUGHT BY ONLINE EDUCATION DURING THE EPIDEMIC AND CONSTRUCTIVE SUGGESTIONS - Жань (Pedagogy and Psychology, 2022)
The emergence of COVID-19 has changed the mode of teaching. From face-to-face communication between teachers and students in the classroom to online communication using the Internet as the medium, teachers and students can communicate through voice and video. As we all know, the effectiveness of communication directly affects the effectiveness of student learning. Can effective communication of learning really be achieved through the Internet? What are the shortcomings of such online teaching methods compared with face-to-face teaching methods? This article analyzes some problems in the communication skills of students in the context of online education, and provides some constructive opinions.